Association Between Maternal Lactate Dehydrogenase Levels and Fetal Outcomes in Preeclampsia with Severe Features - Nurul Robiah Aladawiyah; Arissa Reissa Utami; Dalri Muhammad Suhartomo (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objective: To assess the association between maternal serum lactate dehydrogenase (LDH) levels and fetal outcomes in patients with preeclampsia with severe features.Methods: A cross-sectional analytical study was conducted using secondary medical record data of pregnant women with preeclampsia with severe features treated at Prof. Dr. Margono Soekardjo Hospital, Indonesia, between December 2024 and December 2025. Consecutive sampling was used. Maternal serum LDH levels were categorized using a cutoff of 400 U/L. Associations between LDH levels and fetal outcomes were analyzed using Fisher’s exact test.Results: A total of 50 samples were included, with 10% exhibiting elevated LDH levels. Fisher’s exact test showed a significant association between elevated maternal LDH levels and lower 5-minute Apgar scores (p < 0.05; RR = 2.76). No significant associations were found between maternal LDH levels and gestational age at delivery, fetal complications, or birth weight (p > 0.05).Conclusion: Higher maternal LDH levels in preeclampsia with severe features are linked to lower 5-minute Apgar scores, indicating an association with acute perinatal stress rather than chronic fetal issues. AbstrakTujuan: Penelitian ini bertujuan menilai asosiasi antara kadar serum lactate dehydrogenase (LDH) maternal dengan luaran janin pada pasien preeklampsia dengan gejala berat.Metode: Penelitian analitik cross-sectional ini menggunakan data sekunder rekam medis ibu hamil dengan preeklamsia dengan gejala berat yang dirawat di RSUD Prof. Dr. Margono Soekardjo, Indonesia, pada periode Desember 2024 – Desember 2025. Pengambilan sampel dilakukan secara consecutive sampling. Kadar LDH serum maternal dikategorikan menggunakan nilai ambang 400 U/L. Hubungan antara kadar LDH dan luaran janin dianalisis menggunakan uji Fisher.Hasil: Hasil penelitian menunjukkan bahwa dari 50 sampel yang dianalisis, 10% menunjukkan kadar LDH meningkat. Uji Fisher menunjukkan adanya hubungan yang bermakna antara peningkatan kadar LDH maternal dan skor Apgar menit ke-5 yang rendah (p < 0,05; RR = 2,76). Tidak ditemukan hubungan yang bermakna antara kadar LDH maternal dengan usia kehamilan saat persalinan, komplikasi janin, maupun berat lahir (p > 0,05).Kesimpulan: Peningkatan kadar LDH maternal pada preeklamsia dengan gejala berat berhubungan dengan skor Apgar menit ke-5 yang lebih rendah, yang mencerminkan terjadinya stres perinatal akut dibandingkan gangguan pertumbuhan janin kronik.